Effect of Fish Meal Source on Nursery Pig Performance - A. M. Jones; J. C. Woodworth; R. D. Goodband; M. D. Tokach; S. S. Dritz; J. M. DeRouchey (Kansas Agricultural Experiment Station Research Reports, 2015)
A total of 600 pigs (Exp. 1, n=250, PIC 327 × 1050; Exp. 2, n=350, DNA Line 200 × 400 with an initial BW of 15.6 ± 0.1 and 14.3 ± 0.2, respectively) were used in two 14-d experiments to determine the effects of fish meal source on nursery pig performance. Each experiment had 10 pens per treatment and five pigs per pen. In Exp. 1, pigs were allotted to pens at weaning (d 0) and were fed a common starter diet for 5 d. On d 5, pens of pigs were allotted by BW to experimental diets that were corn and soybean meal-based and contained 10% dried whey. Dietary treatments included a corn and soybean meal-based diet, a diet containing 8.3% HP 300 (Hamlet Protein, Findlay, OH), or diets containing 6% fish meal from one of three sources (IPC 790 Fish Meal, The Scoular Company, Minneapolis, MN; Special Select Menhaden Fish Meal, Omega Proteins, Houston, TX; and Daybrook LT Prime Menhaden Fish Meal, Daybrook Fisheries, Morristown, NJ). The Special Select Menhaden fish meal was from the 2014 catch year, while the LT Prime and IPC 790 were from the 2015 catch year. Samples of each fish meal source were analyzed for total volatile N (New Jersey Feed Laboratories, Inc., Trenton, NJ); a measure of fish meal quality or freshness. All samples of fish meal contained less than 0.15% total volatile N indicating high quality. Results from Exp. 1 indicated that there were no differences observed in ADG or ADFI between any of the treatments. However, pigs fed IPC 790 fish meal had poorer F/G from d 7 to 14 (P<0.049) and overall (P<0.009) compared to pigs fed all other treatments. In Exp. 2, pigs were allotted to pens at weaning (d 0) and were fed a common starter diet for 7 d and then pens were allotted by BW to experimental diets. Fish meal sources were the same as in Exp. 1, except they were all from the 2014 catch year. Dietary treatments included the same corn and soybean meal-based diet and diets with 6% fish meal from Exp. 1. In addition, diets with 3% fish meal were included. From d 0 to 14, a fish meal source × level interaction was observed for ADG and F/G. Pigs fed increasing IPC 790 fish meal had a linear improvement in ADG and F/G; however, for pigs fed either Special Select Menhaden or LT Prime Menhaden fish meals, there was no improvement in performance beyond the 3% inclusion. Traditional measures of fish meal quality (total volatile N) did not appear to be correlated with pig performance in these studies.
Keywords: fish meal; growth; nursery pig; protein quality